Effects of respiratory virus vaccination and bovine respiratory disease on the respiratory microbiome of feedlot cattle - McAtee, Taylor B.; Pinnell, Lee J.; Powledge, Sherri A.; Wolfe, Cory A.; Morley, Paul S.; Richeson, John T. (Frontiers in Microbiology, 2023)
The objectives of this study were to evaluate the impacts of two modified-live virus (MLV) vaccination protocols and respiratory disease (BRD) occurrence on the microbial community composition of the nasopharynx in feedlot cattle. The treatment groups included in this randomized controlled trial included: 1) no viral respiratory vaccination (CON), 2) intranasal, trivalent, MLV respiratory vaccine in addition to a parenteral BVDV type I and II vaccine (INT), and 3) parenteral, pentavalent, MLV respiratory vaccination against the same agents (INJ). Calves (n =525) arrived in 5 truckload blocks and were stratified by body weight, sex, and presence of a pre-existing identification ear-tag. A total of 600 nasal swab samples were selected for DNA extraction and subsequent 16S rRNA gene sequencing to characterize the microbiome of the upper respiratory tract. Nasal swabs collected on d 28 from healthy cattle were used to evaluate the impact of vaccination on upper respiratory tract (URT) microbial communities. Tenericutes were less abundant in INT calves (n = 114; P < 0.05) and this difference was attributed to decreased RA (RA) of Mycoplasma spp. (P = 0.04). Mannheimia and Pasteurella genera had lower RA in INT (P < 0.05). The microbiome in healthy animals on d 28 had increased Proteobacteria (largely Moraxella spp.) and decreased Firmicutes (comprised almost exclusively of Mycoplasma spp.) compared to animals that were treated for or died from BRD (P < 0.05). Cattle that died had a greater RA of Mycoplasma spp. in their respiratory microbiome on d 0 (P < 0.02). Richness was similar on d 0 and 28, but diversity increased for all animals on d 28 (P > 0.05). Cattle that remained healthy throughout the study had a lower Mycoplasma:Moraxella ratio than animals that developed BRD or died (P < 0.05). There was a significant temporal shift in the URT microbiome composition over the first 28 d in the feedlot, in addition to a shift associated with health status during the same period. Furthermore, BRD may have caused alteration of the URT microbiome and administration of INT, but not INJ, influenced microbial community structure.